Touch blue - Lord, Cynthia (Scholastic, 2012)
When the state of Maine threatens to shut down their island's one-room schoolhouse because of dwindling enrollment, eleven-year-old Tess, a strong believer in luck, and her family take in a trumpet-playing foster child, to increase the school's population.